Amyotrophic lateral sclerosis - aetiology, diagnostics and multidirectional, team, long-term care - Kamila Tuzim; Tomasz Tuzim; Magdalena Urbańczuk; Marcin Urbańczuk; Katarzyna Schab (Kazimierz Wielki University, 2018)
Amyotrophic lateral sclerosis (ALS) is a rare neurodegenerative disease of brain motoneurons and spinal cord. The incidence rate of this completely incurable condition amounts to 3 to 5 patients per 100,000 inhabitants and its characteristic feature is progressing muscle weakening that leads to respiratory muscle paralysis and death within 3-4 years. Up to now, etiopathogenesis of ALS is unknown, however, more and more often the role of genotype interaction with environmental factors is suggested. Diagnosing ALS is still based on a correlation of interview and clinical picture with the results of diagnostic imaging, electrophysiological examinations and some serological tests. Despite an enormous progress that occurred in neurobiology and molecular genetics, an effective pharmacotherapy inhibiting the development of the disease has not been developed yet, and the treatment is exclusively based on a systematic symptomatic management. Due to the above, ALS treatment is still a great challenge both for the scientists and clinicians.